A Retrospective Study of Superficial Type Atypical Lipomatous Tumor - Mashima, Emi; Sawada, Yu; Saito-Sasaki, Natsuko; Yamamoto, Kayo; Ohmori, Shun; Omoto, Daisuke; Yoshioka, Haruna; Yoshioka, Manabu; Okada, Etsuko; Aoki, Takatoshi; Hisaoka, Masanori; Nakamura, Motonobu (Frontiers in Medicine, 2020)
Atypical lipomatous tumor (ALT) has been defined as a well-differentiated liposarcoma exhibiting a high frequency of a local recurrence after surgical resection. ALT is mainly classified into deep type and superficial type. Compared with deep type ALT, superficial type ALT is rarely observed. One of the most important issues is that little has been known about superficial type ALT and it is not easy to predict the presence of superficial type ALT before surgical resection. To clarify the clinical manifestations of superficial type ALT, we examined 15 cases with superficial type ALT and 118 cases with benign lipoma, and analyzed their differences of clinical characteristics and MRI findings. In clinical characteristics, the tumor size of superficial type ALT was significantly greater than that of benign lipoma, and superficial type ALT showed a significantly high frequency of the tumor size more of than 4 cm. Superficial type ALT exhibited poor tumor mobility and hardness with elastic soft. In addition, a significantly high frequency of tumor location of superficial type ALT was observed in extremities. Among tumor sites at the trunk, buttocks and shoulder were frequent high location in superficial type ALT. In a magnetic resonance imaging (MRI) examination, superficial type ALT exhibited a significantly higher frequency of the septal structures compared with benign lipoma. The combinations of clinical characteristics, including physical examinations, MRI, and histological examinations, are helpful for the diagnosis of superficial type ALT.